The contribution of public financial policy to achieving economic goals in Algeria - Using the Magic Square of Kaldor for the period 2000/2019- - Lamraoui, salim; Benlaharche, sarah; hassani, abdelakrim (Journal of Research in Finance and Accounting, 2026)
This study aims to highlight the extent of the contribution of public financial policy to achieving economic goals in Algeria - by applying the goals of Magic Square of Kaldor, which are mainly represented in the rates of economic growth, inflation, unemployment and the balance of payments, In order to achieve the objectives of this study, the analytical method was used, To describe and analyze the reality of the indicators of the financial policy tools adopted , and to analyze the implications of the policies adopted on economic performance through the use of reports of national and international statistics. This study concluded that Algeria's financial policy is linked to petroleum tax revenues; With its increase, the state follows an expansionary policy, and when it decreases, the state follows an austerity policy, so that the Algerian economy remains subject to external changes.